Development of an implementation plan for a school-based multimodal approach for depression and suicide prevention in adolescents - Jenniskens, Kristel; Rasing, Sanne; Popma, Arne; Creemers, Daan; Ghalit, Chaimae; van Vuuren, Leonie; Mérelle, Saskia; Spijker, Jan; van Nassau, Femke (Frontiers in Public Health, 2024)
Strong Teens and Resilient Minds (STORM) is a multimodal, school-based approach for depression and suicide prevention in adolescents that is currently implemented in a region in the Netherlands. The STORM approach will be implemented in new regions in the coming years. This study used the implementation mapping protocol to report on the development of the STORM implementation plan. First, a needs assessment was conducted through semi-structured interviews with stakeholders and brainstorming sessions with regional programme leaders in the two regions that started implementing STORM in 2023. This led to the identification of six main barriers to implementation: high level of demands for schools, insufficient understanding of the programme content, insufficient network collaboration, no perceived relative advantage of STORM by stakeholders, lack of attention to sustainability, and high work pressure. Second, performance and change objectives were formulated based on these barriers. For example, a performance objective for potential providers was that they felt supported by STORM. Third, implementation strategies were selected from theory and translated into practical applications through brainstorming sessions with programme leaders. The following strategies were included in the implementation plan: collaborate with similar initiatives within the region, free up time for STORM tasks, tailor strategies, identify and prepare STORM champions, and promote network weaving. Last, a plan to evaluate the implementation of STORM and the application of the STORM implementation plan was formulated. Planned evaluation research will provide more insight into the usefulness and impact of the STORM implementation plan.